Fabrication and upconversion emission processes in nanoluminophores NaYF 4 : Er, Yb and NaYF 4 : Tm, Yb. (1st January 2015) - Giang, Lam Thi Kieu; Anh, Tran Kim; Binh, Nguyen Thanh; Minh, Le Quoc; Marciniak, Lukasz; Łojkowski, Witold
In this paper we present the new results of fabrication, characterisation and upconversion emission process of NaYF4 nanoparticles doped with Er3+ or Tm3+ and Yb3+ as sensitiser. In order to fabricate α–, β–NaYF4 :2%Er3+, 19%Yb3+ and α–, β–NaYF4 :2%Tm3+, 19%Yb3+ nanoparticles the soft template method in isopropylamine at 140C and diethylene glycol (DEG) at 180C has been used. The morphology, structures and emission properties were studied by X–ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and luminescence spectroscopy. The upconversion luminescence (UCL) spectra of α and β crystalline forms of NaYF4 :2%Er3+, 19%Yb3+ and NaYF4 :2%Tm3+, 19%Yb3+ nanoparticles were investigated upon diode laser excitation at 976 nm. The strong emissions in the green and red spectral regions were observed upon this excitation. The spectral lines of the UCL could be assigned to the upconversion radiative transitions of the Er3+ or Tm3+ ions with Yb3+ sensitiser. The upconversion emission spectra dependent on laser excitation powers have been investigated in order to elucidate the upconversion emission paths which could take place. We found the significant influence of the type of nanocrystalline structure on the upconverting radiative transition mechanisms in NaYF4 :2%Er3+, 19%Yb3+ and NaYF4 :2%Tm3+, 19%Yb3+ nanoparticles.